Unraveling Anthropocene Paleoenvironmental Conditions Combining Sediment and Foraminiferal Data: Proof-of-Concept in the Sepetiba Bay (SE, Brazil) - Silva, Layla Cristine da; Alves Martins, Maria Virgínia; Figueira, Rubens; Frontalini, Fabrizio; Pereira, Egberto; Senez-Mello, Thaise M.; Castelo, Wellen Fernanda Louzada; Saibro, Murilo Barros; Francescangeli, Fabio; Mello e Sousa, Silvia Helena; Bergamaschi, Sérgio; Antonioli, Luzia; et al. (Frontiers in Ecology and Evolution, 2022)
The Sepetiba Bay (SB), located in the state of Rio de Janeiro (SE Brazil), is a transitional ecosystem highly anthropized. Because of its great environmental, economic, and social importance, the SB has been the target of several studies to investigate the sources of pollution and their environmental impact. However, studies on the response of foraminifera to pollution are rare. This study applies for the first time in the SB the Ecological Quality Ratio (EQR) based on the biotic index exp(H’bc), related to foraminiferal diversity, coupled with granulometric, mineralogical, and geochemical data and a robust age model (based on 210Pb and 137Cs activity). This study aims to evaluate the paleo-ecological quality status (PaleoEcoQS) along core SP5, collected in the inner central region of the SB. In the sedimentary record of the first half of the 20th century, no foraminifera were found, and the moderate enrichment in lithogenic elements was probably related not only to weathering and erosion of rocks but also to mining activities in the region. From the second half of the 20th century, the study area was under higher marine influence. Progressive siltation took place because of anthropogenic interventions in river courses, eutrophication, and metal pollution. Weak hydrodynamic conditions favored the accumulation of fine-grained sediments and organic matters. In the same period, low diversified benthic foraminiferal assemblages, including mainly opportunist species, were developed. Paleo-ecological conditions inferred by the biotic index exp(H’bc) were poor around 1970 and worsened after the metal spill released by Companhia Ingá Mercantil (a zinc ore processing plant). After that, progressively recovery has led to good ecological conditions in 2015. This study shows how benthic foraminiferal methods could represent a very useful tool to track changes in the evaluation of PaleoEcoQS.